Predicting Repurchase Intentions of Leather Fashion Products: Integrating Brand Perceptions and Product Evaluation Models - Siti Samsiyah Purwaningsih; Sholihati Amalia; Sri Surjani Tjahjawati; Krisna Yudha Bakhti (Jurnal Internasional Penelitian Bisnis Terapan, 2021)
This study examines factors that drive customer repurchase intentions toward leather fashion products by integrating the concept of brand perception and product evaluation. The data were gathered from 297 customers of leather fashion products in Garut, West Java, Indonesia. Partial Least Square was employed to evaluate the effect of brand perception (consisting of brand experience and brand affect) and product evaluation (consisting of perceived value, perceived quality, and price perception) on customer intention to repurchase. The findings reveal that brand perception has a positive significant impact on product evaluation which indirectly influences customer repurchase intention. Theoretically, this study has succeeded in verifying the integration of brand perception and product evaluation to predict customer repurchase intention. Meanwhile, the practical implication lies in the importance of improving product quality and strengthening the brand in order to stimulate the customers’ intention to repurchase.